Take Control of iOS & iPadOS Privacy and Security - Fleishman, Glenn (Take Control Books, 2020)
Master networking, privacy, and security for iOS and iPadOS! Ensuring that your iPhone or iPad's data remains secure and in your control and that your private data remains private isn't a battle--if you know what boxes to check and how to configure iOS and iPadOS to your advantage. While Apple biases security and privacy in your favor, Take Control of iOS & iPadOS Privacy and Security takes you into the intricacies of Apple's choices when it comes to networking, data sharing, and encryption. The book comprehensively covers networking, privacy, and security in iOS 14 and iPadOS 14, answering any question you might have across all of those areas. The book covers Wi-Fi, Bluetooth, and cellular networking; third-party password managers; tracking an iOS device; USB port blocking to prevent brute-force passcode cracking; Low Data Mode for cellular and Wi-Fi data; using the Apple Watch on a Wi-Fi network; configuring and setting up Personal Hotspot and Instant Hotspot; blocking jerks and spam; two-factor authentication with an Apple ID; using AirDrop and AirPlay; solving connection problems; and much more. The book offers insight into what information you may unintentionally expose about yourself, and how to prevent Apple and third parties from gaining access to your details. This includes the several techniques Apple has built into Safari for iOS and iPadOS that prevent advertising and tracking companies from following your actions and connecting your browsing behavior on unrelated sites. You'll learn how to: Troubleshoot problematic Wi-Fi connections. Create and manage passwords for easy entry, including with third-party passwords tools. Understand Safari's blocking techniques and how to review websites' attempts to track you. Work with Find My to meet up and travel with friends and family, and track down lost devices. Master all the options for a Personal Hotspot for yourself and in a Family Sharing group. Share a Wi-Fi password with nearby contacts and via a QR Code. Use the option for COVID-19 contact tracing to preserve your privacy. Stream music and video to other devices with AirPlay 2. Deter brute-force cracking by relying on a USB Accessories timeout. Configure Bluetooth devices. Transfer files between iOS and macOS with AirDrop. Block creeps from iMessage, FaceTime, text messages, and phone calls. Secure your data in transit with a Virtual Private Network (VPN) connection. Protect Apple ID account and iCloud data from unwanted access. Under...